Little Tim and the brave sea captain - Ardizzone, Edward ((New York) : Puffin)
A little boy stows away on a ship, and proves his courage when the ship crashes and is wrecked.
Booklist.
Child Study Children's Book Committee.
5.1
K-3.
K-3
Keywords: Sea stories; Sea stories